Pharmacokinetic assessment of a novel Albendazole- Levamisole combined formulation in cattle: patterns of tissue/parasite accumulation - Cantón, Candela (2025)
The use of anthelmintic combinations is a recognizedstrategy to optimize parasite controland delay resistance. In this context, a new oralformulation combining albendazole and levamisolewas evaluated in cattle. The studies included:(i) assessment of plasma drug profilesfollowing administration of each drug separatelyor in combination; and (ii) analysis of tissueand parasite concentrations of the main analytes in the gastrointestinal system. Plasma pharmacokinetics showed that systemic exposure to each active principle was maintained without adverse interactions. Enhanced concentrations of target analytes were detected in gastrointestinal tissues and parasites following administration of the combined formulation. The highest concentrations were measured within adult nematodes after the treatment with the new combined formulation, with concentrations within target nematode parasites ranging from 8.1 to 11.9 µg/g. These concentrations levels where higher than those recovered after the single treatment (between 0.55 and to 5.3 µg/g). These findings support the potential of this novel combination as an effective alternative for the control of resistant parasites in cattle.